2022
DOI: 10.1172/jci.insight.155944
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive immune responses in vaccinated patients with symptomatic SARS-CoV-2 Alpha infection

Abstract: Benchmarks for protective immunity from infection or severe disease after SARS-CoV-2 vaccination are still being defined. Here we characterized virus neutralizing and ELISA antibody levels, cellular immune responses, and viral variants in 4 separate groups: Healthy control participants weeks (early) or months (late) following vaccination in comparison to symptomatic SARS-CoV-2 infections after partial or full mRNA vaccination. During the study time, most symptomatic breakthrough infections were caused by the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…However, taken together our data suggest that breakthrough infection can occur despite potent adaptive immune responses to the vaccine strain spike protein, even in young healthy boosted VRs. This is in contrast to studies that found lower neutralizing antibody and T cell responses in breakthrough VRs who were infected with the Alpha variant (20)(21)(22) and confirms a study showing high titers of spike-binding antibodies in patients with Omicron breakthrough infections (28). While only 4.4% of the participants in that study had received 3 vaccine doses, all the VRs in our study had received a booster shot.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…However, taken together our data suggest that breakthrough infection can occur despite potent adaptive immune responses to the vaccine strain spike protein, even in young healthy boosted VRs. This is in contrast to studies that found lower neutralizing antibody and T cell responses in breakthrough VRs who were infected with the Alpha variant (20)(21)(22) and confirms a study showing high titers of spike-binding antibodies in patients with Omicron breakthrough infections (28). While only 4.4% of the participants in that study had received 3 vaccine doses, all the VRs in our study had received a booster shot.…”
Section: Discussionsupporting
confidence: 78%
“…Breakthrough infections with the Alpha variant in fully vaccinated individuals have been associated with lower titers of neutralizing antibodies (20)(21)(22) and less robust T cell responses (23). However, given that the Omicron variant has more mutations and evades neutralizing antibody responses better than prior VOCs, the mechanisms of Omicron variant breakthrough infections are likely different.…”
Section: Discussionmentioning
confidence: 99%
“…For comparison between the vaccine virus and VOCs, data were expressed as the percentage of ACE2 inhibition. Live-virus microneutralization assays were performed as described elsewhere, using 2-fold dilutions of plasma incubated with infectious virus and then VeroE6-TMPRSS2 cells to measure cytopathic effect [ 25 ]. Results were expressed as the log 10 -transformed neutralizing antibody (nAb) area under the curve.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, among mRNA-based vaccines, mRNA-1273 appears to display greater efficacy than BNT162b2 [ 74 ]. On the other hand, it is also important to consider the immune response generated by the individual, as there is some evidence suggesting that subjects partially or fully vaccinated with lower virus-neutralizing antibody levels were more likely to be infected by the Alpha variant [ 75 ]. The detection of IgA and IgG in the nasopharyngeal fluid appears to be directly correlated with an improved response against the Alpha variant, supporting the relevance of the humoral response to control this infection [ 76 ].…”
Section: Main Sars-cov-2 Variantsmentioning
confidence: 99%